Efforts of Islamic Education Teachers in Preventing Student Bullying Behavior in High Schools - Anugrah, Muhammad Ichsan; Alizarman, Alizarman; Masriko, Masriko; K, Munawir (International Journal of Multidisciplinary Research of Higher Education, 2021)
Any action that aims to bring down one party with acts of violence or harassment of victims by perpetrators who have power or strength. This study aims to analyze the forms of bullying that occur, to find out the factors that cause students to bully. This study uses a qualitative method with a case study approach. Data sources were taken from two informants through in-depth interviews, one informant was the school principal and the other was an Islamic religious education teacher. The research results obtained are an analysis of bullying behavior which has been studied by researchers, namely in the form of physical contact and verbal form which makes the victims of bullying experience deep trauma so that the role of religious teachers in dealing with bullying problems between students is very important in this case, so religious teachers do socialization related to the dangers of bullying behavior because teachers who act as parents at school are required to provide good treatment so that students who behave as bullies can become good children in socializing, religious teachers must carry out intensive monitoring aimed at students who behave as victims of bullying can be a child who can interact socially well and has a firm soul in dealing with future treatment and can overcome his own problems. The implications of this article are made to find out what forms of bullying are in schools so that the number of victims continues to grow and this must be prevented as soon as possible, so steps are needed to prevent bullying.